The SEO effect. Mapping the optimized landscape around controversial policy issues in Italy - Caroleo, Laura; Giorgi, Giulia; De Amicis, Camilla (Frontiers in Sociology, 2023)
This research investigates the use of SEO (Search Engine Optimization) by political and non-political actors to amplify visibility on search engine results. While there has been much theoretical speculation around the role of SEO techniques in boosting the ranking appearance of a website, few empirical studies have been undertaken to understand the extent to which SEO techniques are used to promote visibility online. This study takes Italy as a case study, to map the information landscape around highly controversial issues: using a combination of digital methods and a tool detecting optimization in websites, our paper aims at examining which actors employ SEO techniques to foster the circulation of their ideas and agendas around hot topics. Our analysis reveals that information channels, institutions and companies are the predominant actors, while political leaders remain in the background. Contextually, data indicate that SEO techniques are employed by a number of recurrent editorial groups, company owners and institutions. Ultimately, we discuss the impact of SEO techniques on the circulation and the visibility of information around relevant policy issues, thus contributing to shaping and influencing public debate and opinion.